Otimização de um sistema de distribuição predial de água fria: estudo de caso - Barrêto Júnior, Manoel (2006)
This dissertation presents a methodology to the optimization of a predial system of cold water distribution. It s about a study of a case applied to the Tropical Buzios Residential Condominium, located in the Búzio s Beach, Nísia Floresta city, the east coast of the Rio Grande do Norte state, twenty kilometers far from Natal. The design of cold water distribution networks according to Norm NBR 5626 of the ABNT - Brazilian Association of Techniques Norms, does not guarantee that the joined solution is the optimal solution of less cost. It s necessary the use of an optimization methodology, that supplies us, between all the possible solutions, the minimum cost solution. In the optimization process of the predial system of water distribution of the Tropical Búzios Condominium, is used Method Granados, that is an iterative algorithm of optimization, based on the Dynamic Programming, that supplies the minimum cost s network, in function of the piezometric quota of the reservoir. For the application of this Method in ramifies networks, is used a program of computer in C language. This process is divided in two stages: attainment of the previous solution and reduction of the piezometric quota of headboard. In the attainment of the previous solution, the minors possible diameters are used that guarantee the limit of maximum speed and the requirements of minimum pressures. The piezometric quota of headboard is raised to guarantee these requirements. In the second stage of the Granados Method, an iterative process is used and it objective is to reduce the quota of headboard gradually, considering the substitution of stretches of the network pipes for the subsequent diameters, considering a minimum addition of the network cost. The diameter change is made in the optimal stretch that presents the lesser Exchange Gradient. The process is locked up when the headboard quota of desired is reached. The optimized network s material costs are calculated, and is made the analysis of the same ones, through the comparison with the conventional network s costs